Experimental and numerical modal analysis of a cross laminated timber floor system in different construction states. (15th August 2022) - Kawrza, Michael; Furtmüller, Thomas; Adam, Christoph
Abstract: This paper addresses the vibration characteristics of a cross laminated timber (CLT) floor in a residential building during three construction states. Experimental modal analyses are carried out on the blank CLT slab, on the slab with added drywall ceiling, and on the slab with drywall ceiling and added floating screed. A reliable numerical model of the system is created with the means of a finite element model updating procedure. This model shows that some experimentally determined modes can be attributed to the dynamic interaction with the shaker used for excitation during the tests. In the finite element model, this effect can subsequently be eliminated. Based on the validated numerical model, the impact of various parameters of the floor construction on the low-frequency footfall sound insulation is investigated. Highlights: Modal analysis of a timber floor system considering in-situ boundary conditions. The influence of three construction states on the modal properties is presented. The installation of a drywall ceiling leads to an increase in certain natural frequencies. Modes due to shaker–structure-interaction are identified numerically. The low-frequency response is predicted using an updated finite element model.